The Antagonism of 5-HT6 Receptor Attenuates Current-Induced Spikes and Improves Long-Term Potentiation via the Regulation of M-Currents in a Pilocarpine-Induced Epilepsy Model - Chaofeng Zhu; Rong Lin; Changyun Liu; Mingzhu Huang; Feng Lin; Gan Zhang; Yuying Zhang; Junjie Miao; Wanhui Lin; Huapin Huang; Huapin Huang; Huapin Huang (Frontiers Media S.A., 2020)
Recent studies have documented that reduced M-current promotes epileptogenesis and attenuates synaptic remodeling. Neurite growth is closely related to the level of 5-HT6 receptor (5-HT6R) in the central nervous system. However, little research is available regarding the relation between 5-HT6R and M-current and the role of 5-HT6R in M-current regulation. Herein, we found that the expression of 5-HT6R was notably increased and the expression of KNCQ2/3, the main components of the M channel, was decreased in a time-dependent manner in pilocarpine-induced chronic epileptic hippocampus. Interestingly, antagonism of 5-HT6R by SB271046 upregulated the expression of KCNQ2 but not KCNQ3. SB271046 greatly alleviated excitatory/inhibitory imbalance and improved the impaired LTP in the chronic epileptic hippocampus. Further mechanism exploration revealed that the above effects of SB271046 can be reversed by the M-channel inhibitor XE991, which also confirmed that SB271046 can indeed improve abnormal M current. These data indicate that the antagonism of 5-HT6R may decrease the excitability of hippocampal pyramidal neurons in chronic epileptic rats and improve the impaired long-term potentiation by upregulating the expression of KCNQ2 in the M-channel.